Ce–Nd separation by solid-phase micro-extraction and its application to high-precision 142Nd/144Nd measurements using TIMS in geological materials. Issue 4 (20th November 2014) - Li, Chao-Feng; Wang, Xuan-Ce; Li, You-Lian; Chu, Zhu-Yin; Guo, Jing-Hui; Li, Xiang-Hui
Abstract : A rapid solid-phase micro-extraction (SPME) technique, using HEHEHP resin as sorbent, is established to completely separate Ce from rare earth element (REE) mixtures. Abstract : In view of the low initial abundance of 146 Sm, 142 Nd anomalies are expected to be extremely small (less than 40 ppm), and their detection requires ultra-precise 142 Nd/ 144 Nd measurements. A rapid solid-phase micro-extraction (SPME) technique, using HEHEHP resin as sorbent, is established to completely separate Ce from rare earth element (REE) mixtures. This technique is applied to ultra-high-precision 142 Nd/ 144 Nd measurements in geological materials. In contrast to the traditional liquid–liquid micro-extraction (LLME) technique, the benefits of the SPME tandem column are high Nd recovery, low residual Ce (Ce/Nd < 10 −6 ), and easy operability. In addition, a single HEHEHP resin column, replacing the traditional two-column scheme (AG 50W + HDEHP resins), is used to further purify Nd by removing Na salt and Sm isobaric interferences. All mean values of 140 Ce/ 144 Nd of geological samples after separation never exceed 0.000010 even though the Ce/Nd ratio of geological materials is >3.0. Thus, 142 Ce interferences on 142 Nd never exceed 1.3 ppm. Ultra-high-precision thermal ionization mass spectrometry analyses of silicate standards show that the internal precision of all runs are better than 4 ppm (2 RSE) for 142 Nd/ 144 Nd values. 142 Nd/ 144 Nd values for JNdi-1, JR-3, and BCR-2 have external precisions of ±4.8, ±4.4, and ±3.9 ppm (2 RSD), respectively. The external reproducibility is sufficient to distinguish and resolve 5 ppm anomalies in 142 Nd/ 144 Nd values.